Project Method as a Means of Developing the Research Activity of a Student - R.Kh.Dzhurayev (Genius Journals, 2023)
The article presents the author's approach to the research activities of younger students, considers teaching them the skills and abilities of research search. The teacher's work on various types of projects and the general structure of research work are presented. Theoretical positions, typical tasks and professional tasks solved by bachelors in specially modeled situations of teacher's professional activity related to the organization of design and research work of schoolchildren are described
Keywords: primary school age; zone of proximal development; independence